Desenvolvimento de software na plataforma NI-LabView para reconhecimento e identificação automática de parâmetros de controle de aerogeradores utilizando dados operacionais - Resende, Hudson da Silva (2016)
Currently, in Brazil and worldwide deployment of central power generation from wind power grows exponentially, however, there is the difficulty in obtaining specific to simulation data (modeling) of the dynamic wind turbines behavior in wind farms to evaluate their impact on the operation of the electricity system that are interconnected. Under the pretext of preserving trade secrets and intellectual property, parameter values such as machine and control systems time constants, are often not available for the studies. Both at the stage of design and after performed the connection of wind farms, impact studies due to the dynamic behavior resulting from disturbances are necessary as requested by regulatory agencies and network operators for evaluation and confirmation of system operating conditions. This work aims to develop a software in NI LabVIEW® platform for recognition and automatic identification of wind turbines models parameters (here called SIPAR1.0) using operational data of a variable speed wind turbine with synchronous technology from the acquisition, processing and evaluation of data quality measuring equipment of electricity and anemometry. With discrete realization on time, and platform based on digital signal processor.